Strategic alliances between banks and fintechs for digital innovation: Motives to collaborate and types of interaction - Milan Frederik Klus; Todor Stefan Lohwasser; Friedrich Holotiuk; Jürgen Moormann (The Journal of Entrepreneurial Finance (JEF), 2019)
In times of digitalization, established firms operating in the financial services sector increasingly form alliances with start-up companies to satisfy the customers' demand for rapid innovation and cope with the growing dynamics of markets. Technology-enabled innovation challenges traditional business models of incumbent institutions (e.g., banks) and requires them to adapt swiftly to the needs of the digital age. However, young firms providing technological solutions for the financial services industry (fintechs) also face difficulties, such as meeting regulatory requirements and winning the trust of potential customers. To compensate for these shortcomings and to exploit synergies, banks and fintechs are increasingly pooling their strengths in alliances. However, so far there is little empirical evidence on the motivation of both sides, banks and fintechs, to collaborate. We use an explorative research design and conduct semi-structured interviews to bridge that gap and shed light on what motivates banks and fintechs to join forces. Building on that, the resulting motives are systematized in a novel conceptual framework and associated with different types of alliances. Our results show that banks are particularly interested in benefiting from rapid innovation without necessarily being involved in its development, while fintechs demand resources and know-how to scale in the highly regulated financial sector. Our results have several practical implications and open up opportunities for future research.
Keywords: G21; G23; G34; M13; 650; Alliances; Digitalization; Banks; Digital Innovation; Fintech; Motives